2016
DOI: 10.4178/epih.e2016056
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Gastrointestinal cancer incidence in Iran, 2001-2010, with joinpoint analysis

Abstract: OBJECTIVESThe main purpose of this study was to evaluate changes in the time trends of stomach, colorectal, and esophageal cancer during the past decade in Iran.METHODSCancer incidence data for the years 2001 to 2010 were obtained from the cancer registration of the Ministry of Health. All incidence rates were directly age-standardized to the world standard population. In order to identified significant changes in time trends, we performed a joinpoint analysis. The annual percent change (APC) for each segment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
0
24
1
Order By: Relevance
“…The first group, which is also the main group, includes studies using the number of deaths, prevalence, incidence rate, and mortality rate as indicators. These studies were designed to evaluate the epidemiology of esophageal cancer and examine the incidence, prevalence, and mortality due to cancers ( 13 - 16 ). The second group included studies concerning disability adjusted life years (DALYs), years of life lost (YLLs), and years lost due to disability (YLD) as health gap indicators.…”
Section: Introductionmentioning
confidence: 99%
“…The first group, which is also the main group, includes studies using the number of deaths, prevalence, incidence rate, and mortality rate as indicators. These studies were designed to evaluate the epidemiology of esophageal cancer and examine the incidence, prevalence, and mortality due to cancers ( 13 - 16 ). The second group included studies concerning disability adjusted life years (DALYs), years of life lost (YLLs), and years lost due to disability (YLD) as health gap indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Although the incidence of GC has decreased in recent years, approximately 990,000 people are diagnosed with GC each year worldwide and about 738,000 of them die due to GC (Karimi et al, 2014). According to the reports from the Iranian Ministry of Health and recent related studies, GI cancers such as EC and GC are the most common cancers in the East-Azarbaijan province (Naghavi, 2001;Somi et al, 2014;Darabi et al, 2016) but few studies have been conducted on the occurrence of GI cancers, their survival rates, and their related risk factors. Also, since the incidence of GI cancers in East-Azarbayjan Province is significantly high (Somi et al, 2014), identifying the potential risk factor of these fatal diseases with appropriate tools is necessary.…”
Section: Determining Risk Factors For Gastric and Esophageal Cancers mentioning
confidence: 99%
“…After the results of many studies on the prevalence and incidence of gastrointestinal cancers in Iran were released, IraPEN was developed in 2015, (7,(22)(23)(24)(25). One of the objectives of this program was to prevent colorectal cancer as this cancer is completely preventable (26).…”
Section: Agenda Settingmentioning
confidence: 99%
“…Changes in individuals' lifestyle, socioeconomic conditions, and increasing life expectancy seem to be associated with the current trend of these cancers (7). A recent study indicated that alcohol consumption and tobacco use are important risk factors of esophagus and gastric cancers (8).…”
Section: Introductionmentioning
confidence: 99%